1991
DOI: 10.1029/91jd01662
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of gravity wave activity and spectra in the mesopause region at Urbana

Abstract: The nightly and seasonal variations in gravity wave activity in the mesopause region are examined by analyzing 60 nights of Na lidar observations obtained during a 5‐year period at Urbana, Illinois. The lidar data were used to calculate the atmospheric density perturbations and their spectra. The atmospheric density variances, density vertical shear variances, vertical wind variances, ω spectra magnitudes, and m spectra magnitudes all exhibit considerable nightly variability as well as strong annual and semian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
174
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(210 citation statements)
references
References 53 publications
26
174
10
Order By: Relevance
“…Placke et al (2011b) in their analysis of GW activity over Andenes (69.3 • N, 16 • E) and Juliusruh (54.6 • N, 13.4 • E) report SAO with maxima around the solstice. As stated earlier, annual and semiannual oscillations in GW activity are anticipated and have been documented in earlier work (e.g., Antonita et al,2008;Clemesha et al, 2009;Mitchell and Beldon, 2009;Beldon and Mitchell, 2009;Senft and Gardner, 1991;Placke et al, 2011b;De Wit et al, 2014b; and references therein); however, this appears to be the first report of a 4-month oscillation in GW momentum fluxes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Placke et al (2011b) in their analysis of GW activity over Andenes (69.3 • N, 16 • E) and Juliusruh (54.6 • N, 13.4 • E) report SAO with maxima around the solstice. As stated earlier, annual and semiannual oscillations in GW activity are anticipated and have been documented in earlier work (e.g., Antonita et al,2008;Clemesha et al, 2009;Mitchell and Beldon, 2009;Beldon and Mitchell, 2009;Senft and Gardner, 1991;Placke et al, 2011b;De Wit et al, 2014b; and references therein); however, this appears to be the first report of a 4-month oscillation in GW momentum fluxes.…”
Section: Discussionmentioning
confidence: 87%
“…Mitchell and Beldon (2009) observed a SAO with maxima at the solstices at Rothera (68 • S, 68 • W) and Beldon and Mitchell (2009) observed the same behavior for Esrange (68 • N) for the fluctuating radial velocities. Senft and Gardner (1991) observed annual and SAO in GW activity at Urbana (40 • N, 88 • W) using Na lidar data to infer atmospheric density perturbations and their spectra. These results are similar to those found by us for middle latitudes, corresponding to SM and CP, the latter mainly in the meridional component of the variances.…”
Section: Discussionmentioning
confidence: 99%
“…Measured amplitudes of a few tenths of percent are consistent with wave amplitudes incident on the duct of a few percent, which seems reasonable. Indeed, typical AGW relative density amplitudes are 5% as measured by Senft and Gardner [1991] with a Na lidar over Urbana. Perhaps, more relevant data are those of Gardner and Voelz [1987] who measured the seasonal characteristics of monochromatic waves seen over Urbana using a Na Table 3 …”
Section: Wave Amplitudes and Propagation Directionsmentioning
confidence: 99%
“…[35] Gardner and Shelton [1985] and Senft and Gardner [1991] showed that the solutions to (A3) and (A4) are accurately represented by the equations…”
Section: Appendix Amentioning
confidence: 99%